Amoxicillin and Clarithromycin Mucoadhesive Delivery System for Helicobacter pylori Infection in a Mouse Model: Characterization, Pharmacokinetics, and Efficacy - Isabel Villegas; María Ángeles Rosillo; Catalina Alarcón-; Victoria Vázquez-Román; Maria Llorente; Susana Sánchez; Ana Gloria Gil; Pilar Alcalde; Esther González; Elisabet Rosell; Carles Nieto; Francisco Fernandez-Campos (MDPI AG, 2021)
Helicobacter pylori is the main pathogen responsible for gastric ulcers and a predisposing factor of stomach cancer. Although current treatment is usually successful, it requires high doses and frequent administration. An innovative mucoadhesive system (Mucolast®) loaded with amoxicillin and clarithromycin is proposed to improve the efficacy of treatment against H. pylori. The drug product was optimized based on its viscoelastic properties to obtain long-term stability of the vehicle. The drug release mechanisms were different for both antibiotics based on their solubilization status. A systemic and stomach pharmacokinetic profile was obtained after three different doses were administered to mice, obtaining similar systemic exposure levels but an increase in drug concentration in the stomach. The efficacy results in mice infected with H. pylori also demonstrated the superiority of the antibiotics when administered in Mucolast®, as shown by the bacterial count in stomach tissue and under histopathological and biochemical evaluation. The proposed treatment was efficacious and safe and is presented as a realistic alternative to current treatment options to improve patient compliance and to reduce bacterial resistance.